2012
DOI: 10.1177/0883911512461108
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility studies of poly(ethylene glycol)–modified titanium for cardiovascular devices

Abstract: The rapid protein adsorption on a material surface causes blood coagulation, platelet activation, and complement system activation, which poses a risk for failure of cardiovascular devices. In this study, a chemically hydroxylated titanium surface was aminosilanized and covalently grafted with poly(ethylene glycol). The reaction conditions on the grafted quantity were studied by the respective amine and carboxyl densities. The blood compatibility of the PEGylated surfaces with different poly(ethylene glycol) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Poly(ethylene glycol) (PEG), an effective and popular antifouling polymer, has been widely used for the surface modication of biomaterials, to improve the blood compatibility. [13][14][15][16] It was reported that immobilized PEG has an outstanding hydrophilicity, which leads to a lower protein adsorption and lower platelet attachment, due to the large repulsive forces existing between the plasma and the thin layer of water tightly bound to them, resulting in the improved blood compatibility. 17,18 Many approaches have been developed to immobilize PEG on a titanium surface, to enhance the anti-coagulation and reduce non-specic protein adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(ethylene glycol) (PEG), an effective and popular antifouling polymer, has been widely used for the surface modication of biomaterials, to improve the blood compatibility. [13][14][15][16] It was reported that immobilized PEG has an outstanding hydrophilicity, which leads to a lower protein adsorption and lower platelet attachment, due to the large repulsive forces existing between the plasma and the thin layer of water tightly bound to them, resulting in the improved blood compatibility. 17,18 Many approaches have been developed to immobilize PEG on a titanium surface, to enhance the anti-coagulation and reduce non-specic protein adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Many antibacterial agents that can endow dental implants with antibacterial activity have been actively studied too, but these agents lack biocompatibility. 30,38 Cytotoxicity and internal organ injury 2,39 caused by the as-prepared surfaces are problems that must be solved. 40,41 The cytotoxicity toward the mouse osteoblast-like MC3T3-E1 cell line, as another crucial factor, should be evaluated with caution once a newly modified Ti is used as a DI.…”
Section: Resultsmentioning
confidence: 99%
“…These amines can act as a starting point for covalent grafting with poly(ethylene glycol) to endow the surface with antifouling properties. 30,31…”
Section: Introductionmentioning
confidence: 99%
“…Acid Orange II (AO II, Sigma-Aldrich, USA) was implemented to quantify the surface amino groups of the coatings [ 25 ]. Micro BCA protein assay kit was used to quantify the phenolic hydroxyl/quinone groups of the coatings as the following steps.…”
Section: Methodsmentioning
confidence: 99%